2015
DOI: 10.1007/s00059-015-4306-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Exo-Seal® and Angio-Seal® for arterial puncture site closure

Abstract: In the present study, there were no significant differences found regarding the occurrence of hematoma > 5 cm, major bleeding, false aneurysm, and device failure between Angio-Seal(®) and Exo-Seal(®) 24 h after device implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…They concluded that VCDs were noninferior to MC in terms of vascular access site complications and reduced time to hemostasis. 33 Ketterle et al 16 published a prospective, single-blinded multicenter trial comparing an anchor/plug-mediated VCD (Angio-Seal) and an extravascular VCD (Exoseal) with one another, with primary end points being access site-related complications (ie, hematoma at least 5 cm in size, significant groin bleeding, pseudoaneurysm, and device failure) after coronary angiography or intervention. The results demonstrated that the incidence of hematoma was lower in the Exoseal group compared with the Angio-Seal group (1.3% vs 1.9%), that the incidence of pseudoaneurysm was lower in the Exoseal group compared with the Angio-Seal group (1.3% vs 2.5%), and that there was a trend for higher device failure rates requiring MC in the Exoseal group compared with the Angio-Seal group (5.2% vs 1.2% ; P ¼ .06).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that VCDs were noninferior to MC in terms of vascular access site complications and reduced time to hemostasis. 33 Ketterle et al 16 published a prospective, single-blinded multicenter trial comparing an anchor/plug-mediated VCD (Angio-Seal) and an extravascular VCD (Exoseal) with one another, with primary end points being access site-related complications (ie, hematoma at least 5 cm in size, significant groin bleeding, pseudoaneurysm, and device failure) after coronary angiography or intervention. The results demonstrated that the incidence of hematoma was lower in the Exoseal group compared with the Angio-Seal group (1.3% vs 1.9%), that the incidence of pseudoaneurysm was lower in the Exoseal group compared with the Angio-Seal group (1.3% vs 2.5%), and that there was a trend for higher device failure rates requiring MC in the Exoseal group compared with the Angio-Seal group (5.2% vs 1.2% ; P ¼ .06).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, there is a low incidence of vascular complications. 5,[13][14][15][16][17][18] Vascade Vascular Closure System (Cardiva Medical, Inc, Santa Clara, Calif; Fig 4) is a passive approximator that deploys a collagen plug over the arteriotomy, causing tamponade of the puncture site as a result of expansion of the plug. A low-profile disc abuts the wall, and a collagen plug is deployed over the arteriotomy.…”
mentioning
confidence: 99%
“…Ketterle et al [ 19 ] investigated about the complications rate differences comparing an anchor/plug-mediated VCD (AngioSeal) and an extravascular VCD (Exoseal). The incidence of haematoma and pseudoaneurysm was lower in the Exoseal group compared with the AngioSeal group (1.3% vs 1.9% and 1.3% vs 2.5%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…A comparative study of the efficacy of the ExoSeal extrafemoral vessel closure device with the well-validated AngioSeal plug-anchor system for vessel closure after coronary angiography and PCI showed that the use of ExoSeal was no worse than treatment with AngioSeal in terms of bleeding, hematoma, false aneurysms, and device failure. The use of ExoSeal was associated with a higher, although not significant, rate of device failure and significantly less pain as measured by the Borg scaleccone [12].…”
Section: Discussionmentioning
confidence: 81%